The Response of Milenial Muslim Generations to The Tradition of Kungkum Purnama in Banjarpanepen, Banyumas, Indonesia - Saridin Saridin; Agus Ujianto; Abdul Basit (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2021)
Islam entered the island of Java with the condition that the people already have traditions. One of the traditions that still exist today is Kungkum Purnama in Kalicawang, Banjarpanepen Sumpiuh Village, Banyumas District. The Kungkum Purnama tradition is carried out every year in the month of Sha’ban as a form of welcoming the month of Ramadan for Muslims. The implementation of the Kungkum Purnama tradition is followed by village communities who are not only Muslim, but also those who are non-Muslim or religious. It cannot be denied that the Muslim millennial generation is one of the heirs to tradition. This study aims to describe the response of the Muslim millennial generation to the kungkum purnama tradition. In practice, researchers used qualitative research methods of field research type. Data were collected by means of observation, interviews and documentation. The analysis was carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results showed that the Kungkum Purnama tradition is a form of acculturation of Islam with Banyumasan culture, which contains social and religious values, namely Islamic syiar, to welcome Ramadan, friendship, and clean oneself. The response of the Muslim millennial generation shows their view of the kungkum purnama tradition. From a religious perspective, the practice of the kungkum purnama tradition on the other hand contains teachings that are contrary to Islamic teachings. From a cultural point of view, the kungkum purnama tradition is a local tradition and a tourist attraction that needs to be preserved. From a social point of view, the kungkum purnama tradition contains the values of cooperation, mutual cooperation, and togetherness